Current Density of AlxGa1-xAs/GaAs Superlattice - Obaid, Ahmed Z.; Abdul-Ameer , Nidhal M.; Abdul-Hasan, Shaymaa Q.; Salman, Ebtisam M-T.; Abdulrida, Moafak C. (Iraqi Journal of Physics, 2024)
Theoretically, the AlxGa1-xAs/GaAs superlattice is studied as a function of optical energy with and without bias. The transfer matrix approach has determined the transmission coefficient and resonant tunnelling current density. The number of barriers is estimated at N = 3, and the concentration ratio (the mole fraction value) x at 0.1, 0.2, and 0.3 is fixed. The number of cells in the well is established at (ncw) = 5, while the number of barrier cells (ncb) is changed from 1 to 5 for both biases. This study shows that the change in the number of barrier cells plays a crucial role in the tunnelling of charge carriers and the transmission probability of charge carriers through the depletion regions. Thus, changing the current density is based on the purpose to be applied. In addition, the values ​​of current density at the reverse bias are higher than that in the forward bias, which is explained by the bias controlling the energy levels of the superlattice. It is worth noting that there are many practical applications in which this system can be used, including solar cells, detectors, and light-emitting diodes.